Accuracy Analysis and Improvement of Calculation Method of Gear System Dynamics Equation - Song Huan; Wu Liyan; Liu Lan; Wang Haiwei (Jixie chuandong)
Taking the single-stage gear rotor system as the research object,a generalized finite element model with total freedom is established. The calculation speed and the accuracy of Newmark method and Fourier series method are compared in solving dynamics equation of gear system. An improved Fourier series method is proposed,which has less calculation time and higher calculation accuracy.